Electrochemical properties of fuel cell catalysts loaded on carbon nanomaterials with different geometries. (June 2015) - Suda, Yoshiyuki; Shimizu, Yoshiaki; Ozaki, Masahiro; Tanoue, Hideto; Takikawa, Hirofumi; Ue, Hitoshi; Shimizu, Kazuki; Umeda, Yoshito
Abstract: PtRu or Pt catalysts were supported on four types of carbon nanomaterials with different shapes, sizes, and graphitic and electrical properties, and their resulting catalytic activities were evaluated by electrochemical methods. The carbon nanomaterials used included two types of particles: Arc Black (AcB) and Vulcan XC-72R (Vulcan), and two types of nanofibers: carbon nanocoils (CNC) and VGCF-X. Pt and Ru were loaded onto the nanomaterials by a reduction method using sodium borohydride. Transmission electron microscopy and X-ray diffraction (XRD) revealed the PtRu catalyst particles to be 4–6 nm in diameters. The shifts in the Pt(1 1 1) XRD peak of the catalysts on CNC and VGCF-X were larger than those on AcB and Vulcan, indicating a higher degree of alloying between Pt and Ru. The diameters of the CNC-supported Pt and PtRu catalyst particles had the narrowest distributions and were constant within the range of catalyst loadings investigated. Electrochemical studies of the catalysts during methanol oxidation were carried out using cyclic voltammetry. The catalyst particles supported on CNC and VGCF-X exhibited higher catalytic activity than those on AcB and Vulcan. The effect of the surface area of the carbon nanomaterials on the catalytic activity is discussed.